REFLECTIVE THINKING OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING NUMERACY PROBLEMS VIEWED FROM MATHEMATICAL ABILITY - Nisak Ayu Nur Arofah; Rooselyna Ekawati; Abdul Haris Rosyidi (Journal of Mathematics Education and Science, 2026)
This research aims to explore in depth the reflective thinking processes of junior high school students in solving numeracy problems based on mathematical ability. The study employed a qualitative approach with a case study design involving six female students from class IX H of SMP Negeri 31 Surabaya, consisting of two high-ability students, two medium-ability students, and two low-ability students selected through purposive sampling. Data collection was conducted through the Mathematical Ability Test, the Numeracy Problem Test in an algebraic context, and semi-structured interviews, and the data were analyzed descriptively and qualitatively following the Miles and Huberman model, with source triangulation to ensure data validity. The research findings reveal significant differences in reflective thinking characteristics across mathematical ability categories. High-ability students demonstrated comprehensive reflective thinking with strong metacognitive awareness, capable of accurately identifying variables, flexibly planning strategies, and conducting thorough evaluations, including exploration of alternatives. Medium-ability students had strong foundations in reflective thinking but tended to perform procedural checks without in-depth exploration, indicating a transitional stage in metacognitive awareness development. Low-ability students experienced significant limitations in reflective thinking and metacognitive awareness, exacerbated by low self-confidence. This research concludes that differentiated learning tailored to students' ability levels is necessary: low-ability students require intensive scaffolding, medium-ability students need guidance in transitioning from procedural to strategic reflection, and high-ability students require complex challenges to optimize their metacognitive abilities.